2018
DOI: 10.1155/2018/1431396
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcription Factor-Related Regulatory Networks Based on Bioinformatics Analysis and Validation in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) accounts for a significant proportion of liver cancer, which has become the second most common cause of cancer-related mortality worldwide. To investigate the potential mechanisms of invasion and progression of HCC, bioinformatics analysis and validation by qRT-PCR were performed. We found 237 differentially expressed genes (DEGs) including EGR1, FOS, and FOSB, which were three cancer-related transcription factors. Subsequently, we constructed TF-gene network and miRNA-TF-mRNA ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…TRRAP/KAT5, which activates TOP2A, has been reported to inhibit HCC cell growth through induction of p53-independent and p21-independent senescence (Kwan et al, 2020). CCNB2, CDC20 and PRC1 are the three most commonly reported upregulated genes in HCC through bioinformatics analyses (Chen et al, 2016a;Gao et al, 2018;Li et al, 2014;Liu et al, 2018;Wang et al, 2019b). CCNB2, as a component of the cell cycle regulatory machinery, is associated with the Golgi region (Draviam et al, 2001;Jackman, Firth & Pines, 1995) and plays an important role in regulating the G2/M transition (Gui & Homer, 2013;Li et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…TRRAP/KAT5, which activates TOP2A, has been reported to inhibit HCC cell growth through induction of p53-independent and p21-independent senescence (Kwan et al, 2020). CCNB2, CDC20 and PRC1 are the three most commonly reported upregulated genes in HCC through bioinformatics analyses (Chen et al, 2016a;Gao et al, 2018;Li et al, 2014;Liu et al, 2018;Wang et al, 2019b). CCNB2, as a component of the cell cycle regulatory machinery, is associated with the Golgi region (Draviam et al, 2001;Jackman, Firth & Pines, 1995) and plays an important role in regulating the G2/M transition (Gui & Homer, 2013;Li et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…The variation in these results could be attributed to the different sample sizes and sequencing databases. A review of the literature revealed that CCNB2 expression is increased in HCC tissues compared to adjacent nontumor tissues [33], and CCNB2 is a target molecule following knockdown of XPOT [34], TPX2 [35], KPNA2 [36], and TMEM9 [37]. The prognostic value and target therapy of the hub genes for HCC patients remain to be confirmed by further clinical studies.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…9 Over the past decades, microarray technology and bioinformatics have been extensively applied to identify the molecular mechanisms of HCC, which provide strong research support for the diagnosis, treatment, and prognosis of HCC. 10 Because of the ability to process a large number of datasets quickly, integrated bioinformatics analysis and microarray technology have allowed researchers to comprehensively identify the functions of numerous differentially expressed genes (DEGs) in HCC, and they help researchers explore the complicated process of HCC occurrence and development. 10,11 A work by He et al 12 identified four hub genes and two important pathways in the development of HCC from cirrhosis from one Gene Expression Omnibus (GEO) dataset using a bioinformatics method, including DEG screening, enrichment analyses, and construction of a protein-protein interaction (PPI) network.…”
Section: Introductionmentioning
confidence: 99%